Socioeconomic analysis of the food security status of maize farming households in giwa local government area of kaduna state, nigeria - Oyakhilomen , Oyinbo; Juliet, Jonathan (Journal of Management and Science, 2013)
his study specifically examined the food security status of the maize farming households, their perception on the contribution of maize farming to their households food security status and the determinants of the food security status of the maize farming households in the study area. Primary data collected from a sample size of 100 maize farming households were employed in the study and the data were analysed using descriptive statistics, food security index and logit regression. The result showed that 54% of the maize farming households was food secure while 46% were food insecure. The maize farming households perceived maize farming to be important in contributing to their household food security. The factors significant in influencing food security in the study area were household size, household income, farming experience, association, extension, education and farm size. It was recommended that farmers should adopt proper maize farming management practices aimed at high intensity of maize production which will serve as maize production offers an opportunity for increasing household food security.